Investigation on mixed oil-cement for wellbore integrity using acoustic velocity - Ridha, S. (Trans Tech Publications Ltd, 2017)
Oilwell cementing is part of completing a well prior to production. As a casing is installed after a section of the well is drilled, cement is pumped downhole. Reservoir fluid such as oil which may encroach into the wellbore due to naturally fractured or unconsolidated formation would mix with the cement pumped downhole. Recent studies have shown that the presence of oil affect cement quality to an extent where the cement compressive strength is greatly reduced. Early detection of possible oil contamination into cement may prevent well integrity problem. With intense application of acoustic principle into wellbore, however, not many references available to detect the presence of oil in cement system using this principle. This study investigates whether acoustic waves can detect oil in cement. Class G cement is mixed with both water and brine where crude oil is then added to the mixture. The resulting slurry were cured using High Pressure High Temperature (HPHT) curing chamber at 120°C and 4,000 psi for 24 hours and is then cored into 1-inch cylinder. SonicViewer-SX is used to propagate acoustic waves through the core sample where the transit time is recorded and analyzed. It is found that oil can be detected in cement using acoustic waves since oil-filled samples have slower P-waves and S-waves velocities than cement-filled samples. The case is also proven when water is replaced by brine as the mixing fluid which oil-filled samples have lower P-waves and S-waves velocities to that of cement-filled samples. © 2017 Trans Tech Publications, Switzerland.